Areas of energy advantage for flowsheets of separation modes for mixtures containing components with similar volatilities - M. E. Peshekhontseva; M. A. Maevskiy; I. S. Gaganov; A. V. Frolkova (Тонкие химические технологии, 2020)
Objectives. The conditions for the effective application of the sharp distillation technique (without a component distributed between the distillate and bottom flows) for the separation of quaternary zeotropic mixtures containing components with similar volatilities were determined. The area of energy advantage for the flowsheet based on the preliminary fractionation of the mixture, compared with the flowsheet, the first distillation column of which works based on the indirect separation mode, was identified for an ethyl acetate–benzene–toluene–butyl acetate system. Energy savings of up to 20% were achieved. The direct and indirect distillation modes can become competitive when the point of the original composition is located near single K-surfaces or in a region with a different ratio of distribution coefficients. Sharp distillation is not suitable for the separation of a mixture containing a pair of components exhibiting relative unity volatility with medium boiling points.Methods. The mathematical modeling in the Aspen Plus V.10.0 software package was chosen as the research method. The simulation was based on the Wilson local composition equation. The relative errors in the description of the phase equilibrium did not exceed 3%.Results. The structure of the vapor–liquid equilibrium diagram and diagram of surfaces of the unit component distribution coefficients were studied for the ethyl acetate–benzene–toluenebutyl acetate and acetone–toluene–butyl acetate–o-xylene systems. Flowsheets based on the sharp, indirect (both systems), or direct (second system) distillation modes were proposed. The distillation process was simulated, and the parameters of the column work were determined (the quality of the substances meets the State Standard requirements of the Russian Federation for minimal energy consumption).Conclusions. Recommendations regarding the use of sharp distillation for the separation of quaternary mixtures containing components with similar volatilities were devised.